Mesoporous silica aerogel reinforced dental composite: Effects of microstructure and surface modification. (January 2022) - Aminoroaya, Alireza; Bagheri, Rouhollah; Nouri Khorasani, Saied; Talebi, Zahra; Derakhshanfar, Parham; Esmaeely Neisiany, Rasoul
Abstract: A mesoporous silica aerogel (SiA) with a high specific surface area was synthesized through the sol-gel process and subsequently modified with two different silane-based modifiers to reveals the effect of microstructure and surface modification on the fracture mechanics of a dental composite. The synthesized and modified aerogel were characterized using field-emission scanning electron microscopy (FESEM), nitrogen adsorption-desorption, and Fourier-transform infrared spectroscopy (FTIR). The prepared aerogels were then incorporated within methacrylate-based dental composites with the filler content of 0–35 wt%. Flexural modulus (FM) and Flexural strength (FS) were evaluated by the three-point bending test. The fracture toughness (FT) of the composites was evaluated by single edge V-notched beam (SEVNB) flexure test, while FESEM was employed to investigate the fracture surface morphology of the composites. Furthermore, the wettability of the composites was assessed according to the sessile drop method. The characterization of synthesized aerogels revealed the formation of SiA with a surface area of 550–560 m 2 /g and porosity of 77%, while FTIR results confirmed the successful modification. Statistical analysis (ANOVA, p ≤ 0.05, and n = 5) revealed that FM significantly enhanced (from 1.43 GPa to 2.66 GPa) as filler content increased over 0–30 wt%, and FS improved (from 80 to 95 MPa) as filler content increased over 0–15 wt%. Furthermore, the modification of aerogels improved both fracture characteristics and the wettability of the composites. The FT evaluations and fractography analysis revealed that the mesoporous structure of the fillers mainly dominated the filler-matrix adhesion strength at the same filler content. Graphical abstract: A mesoporous silica aerogel (SiA) with a high specific surface area was synthesized through the sol-gel process and subsequently modified with two different silane-based modifiers to reveals the effect of microstructure and surface modification on the fracture mechanics of a dental composite. Image 1 Highlights: High surface-area mesoporous silica aerogel (SiA) was synthesized as dental reinforcing filler. SiA improved the flexural properties, fracture toughness, and contact angle of dental composites. SiA microstructure dominates the fracture mechanics of methacrylate dental composites. SiA surface modification influences the methacrylate resin diffusion to the filler porosity.